Psychosocial functioning of the patient with spinal cord and whiplash injury: A case report - Sabir Zaman; Basharat Hussain; Shahid Irfan; Muhammad Muslim Khan (Journal of the Pakistan Medical Association, 2021)
Published in August 2021.